2014
DOI: 10.1016/j.mjafi.2013.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Mesh repair of vaginal wall prolapse

Abstract: Perigee ProlapseMesh repair a b s t r a c t Background: Over the last decade, mesh augmented surgical repair is being increasingly used in pelvic organ prolapse. Perigee and Apogee are comprehensive, single-use needle suspension kits that provide a standardized delivery method for mesh or graft-augmented repairs. This study has been carried out to study the safety and efficacy of the Perigee and Apogee mesh repair systems.Methods: 10 cases of posterior vaginal wall prolapse with or without Apical prolapse unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
2
1
1
Order By: Relevance
“…In a single TVM series using the Perigee technique, the average blood loss was found to be 180 ml [5], which was much higher than in our TVM data series (83 ml), and the mean procedure duration was also shorter in the TVM group (39 min vs. 60.9 min) [54]. In our retrospective study, we found no significant alterations between the prosthesis and natural tissue reconstructive operations in length of operation and blood loss.…”
Section: Discussioncontrasting
confidence: 56%
“…In a single TVM series using the Perigee technique, the average blood loss was found to be 180 ml [5], which was much higher than in our TVM data series (83 ml), and the mean procedure duration was also shorter in the TVM group (39 min vs. 60.9 min) [54]. In our retrospective study, we found no significant alterations between the prosthesis and natural tissue reconstructive operations in length of operation and blood loss.…”
Section: Discussioncontrasting
confidence: 56%
“…A műtét elvégzéséhez szükséges idő érthető módon szignifikánsan hosszabbnak mutatkozott a TVM-csoportban, mint a háló nélküli csoportban (39,01 ± 5,95 min vs. 35,55 ± 6,92 min), viszont az általunk mért műtéti idő a TVM-csoportban a nemzetközi irodalomban szereplőnél jobb volt (60,9 min) [30]. A becsült vérveszteség tekintetében a két csoport között nem találtunk jelentős eltérést, és az általunk becsült vérzés az A nemzetközi tanulmányokkal megegyezően saját vizsgálatunk során is azt az eredményt kaptuk, hogy az alkalmazott hálóműtét rekonstruktív képességben mind a süllyedést helyreállító, mind a genuin stresszincontinentiára kifejtett hatás tekintetében szignifikánsan jobb, mint a háló nélküli Kelly-Stoeckel-plastica.…”
Section: Megbeszélésunclassified
“…Benson et al [ 5 ] show that the surgical technique concerning the use of meshes has better outcomes within apical vaginal prolapse compared to vaginal surgery with a sacrospinous fixation. A large amount of papers support the use of mesh in surgery; in particular, the guidelines for vaginal prolapse surgery show that meshes are better performing with respect to other traditional techniques [ 6 ]. In comparison to old techniques the innovative surgical procedure for transvaginal prolapse (Apogee, Perigee, and Prolift) has shown good results in short term, despite having significant complications such as buttock pain, vaginal erosion, erosion of the bladder, and infection and therefore should be used carefully.…”
Section: Introductionmentioning
confidence: 99%